Managed Labor Migration in Afghanistan : Exploring Employment and Growth Opportunities for Afghanistan - Holzmann, Robert (World Bank, Washington, DC, 2018)
Afghanistan’s economic prospects are dim and its growth options limited. This puts pressure on the labor market, with 400,000 new entrants joining the labor force annually. As in the past, this will likely lead to mostly illegal emigration with limited employment prospects and wages in neighboring countries (Pakistan, Iran) and beyond. This is unfortunate given Afghanistan’s geographic proximity to the world’s third largest migration destination region behind North America and Europe: the countries of the Gulf Coordination Council (GCC). For some time now, various Asian countries have used managed labor migration as a means to secure temporary and legal jobs for their surplus labor, garnering higher wages and opportunities to transfer income back to their families, save for future investments, and gain work experience and higher skills. Managed labor migration based on well-designed bilateral labor agreements that reflect the objectives of both the labor-sending and labor-receiving country could open opportunities for Afghanistan in GCC countries and even in higher wage labor markets, provided that adequate labor-sending systems are in place. This paper explores the use of managed labor migration as an instrument for employment for the Afghan labor force and for economic growth. It investigates the supply of and demand side for managed migration flows, estimates the impact on the volume of remittances sent back, and examines the possible impact of formal labor migration opportunities on skills formation of migrants and of the labor force remaining home. These quantitative profiles of remittances and skills are explored with a country-calibrated computable general equilibrium model to estimate the impact on output, economic growth, and other relevant economic outcomes; they may trigger policy action to make managed labor migration a reality in Afghanistan.